2022
DOI: 10.1039/d2nj02577a
|View full text |Cite
|
Sign up to set email alerts
|

A recyclable graphene/Ag/TiO2 SERS substrate with high stability and reproducibility for detection of dye molecules

Abstract: Few-layer chemical vapor deposition (CVD) graphene was successively wet transferred on magnetron sputtering Ag/TiO2 film to develop a recyclable surface-enhanced Raman scattering (SERS) substrate with high sensitivity, stability and reproducibility...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…25 The graphene/Ag/ TiO 2 composite substrate prepared by Wang et al still maintained good SERS performance after repeated use for 5 times. 26 Compared with other semiconductor materials, MoS 2 had a good response to both ultraviolet and natural light. The combination of MoS 2 and Ag NPs forms a Schottky barrier at the interface where the two contact, plays the role of electron sinking, accelerates the electron−hole pair separation generated by visible light excitation, and reduces recombination.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The graphene/Ag/ TiO 2 composite substrate prepared by Wang et al still maintained good SERS performance after repeated use for 5 times. 26 Compared with other semiconductor materials, MoS 2 had a good response to both ultraviolet and natural light. The combination of MoS 2 and Ag NPs forms a Schottky barrier at the interface where the two contact, plays the role of electron sinking, accelerates the electron−hole pair separation generated by visible light excitation, and reduces recombination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kandjani et al reported that the Ag composite ZnO nanorod array structural material as the SERS substrate had good stability and self-cleaning ability . The graphene/Ag/TiO 2 composite substrate prepared by Wang et al still maintained good SERS performance after repeated use for 5 times . Compared with other semiconductor materials, MoS 2 had a good response to both ultraviolet and natural light.…”
Section: Introductionmentioning
confidence: 99%
“…By far, a range of wide bandgap semiconductors, specifically those complaining with cost-effectiveness and low toxicity criteria, have been tested for the SERS metrology. ,, Particularly, metal-oxide semiconductors, e.g., ZnO and TiO 2 , were employed as efficient SERS substrates. These materials are also effective photocatalysts, and because of their self-cleaning properties, these oxides were suggested to be promising recyclable SERS substrates. Notably, ZnO exhibits a higher refractive index and stronger optical absorption, making it more efficient for SERS applications. Additionally, its surface has more electrochemically active sites than that of TiO 2 , which improves SERS signals and photocatalytic activity on its surface due to the charge transfer mechanism. ,, In its turn, noble metal nanostructures, including Ag, Au, etc., have been used extensively as SERS substrates too, due to their excellent LSPR properties, featuring intense absorption and “hot spots”, resulting in an enhanced local electromagnetic field providing conditions for ultrasensitive SERS detection. , Thus, the current state of the art is in designing heterogeneous composites combining the unique LSPR characteristics of the noble metals with the self-cleaning capabilities of the metal oxide nanostructures in order to produce highly sensitive and recyclable SERS substrates with tunable characteristics for long-term practical applications. ,,,,, …”
Section: Introductionmentioning
confidence: 99%
“…They exhibited an LOD lower than 10 −12 mol/L for rhodamine 6G (R6G) molecule in a recyclable manner [ 30 ]. Other Ag-TiO 2 -based recyclable SERS substrates are reported in references [ 31 , 32 , 33 ]. In the present work, silver monolayers of different thicknesses were prepared to investigate the resulting Raman spectra.…”
Section: Introductionmentioning
confidence: 99%